Composite material with excellent heat insulation performance

By adopting a composite material structure on the surface of the aircraft, combined with expanded fireproof coatings, metal titanium foils, aerogel felts and phase change materials, the problems of large weight and poor stability of the thermal insulation and protection structure in the prior art are solved, and efficient thermal insulation and fire resistance are achieved, which is suitable for high-temperature environments.

CN119910985AActive Publication Date: 2025-05-02SOUTHWEST TECHNICAL ENGINEERING RESEARCH INSTITUTE OF CHINA SOUTH IND GROUP

Patent Information

Application Number
CN202510211484.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-05-02
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

In the prior art, the thermal insulation and protection structure on the surface of the aircraft under an aerodynamic thermal environment has problems such as large weight, high space occupancy, large ablation reversal, poor long-term stability, and poor thermal insulation performance, which cannot meet the needs of long-term flight operations.

Method used

A composite material structure is adopted, including a fireproof layer, a transition layer, a first protective layer, a first thermal insulation layer, a second thermal insulation layer and a second protective layer. Excellent thermal insulation and fire resistance performance is achieved through the combination of expanded fireproof coating, metal titanium foil, aerogel felt and phase change material.

Benefits of technology

The composite structure exhibits excellent thermal insulation and fire resistance under high temperature environments, with light weight, thin thickness and good long-term stability. It is suitable for high temperature environments between 800℃ and 1200℃, effectively protecting the surface of the aircraft.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119910985A_ABST
    Figure CN119910985A_ABST
Patent Text Reader

Abstract

The invention provides a composite material with excellent heat insulation performance, which relates to the field of fireproof heat insulation structures, and sequentially comprises a fireproof layer, a transition layer, a first protection layer, a first heat insulation layer, a second heat insulation layer and a second protection layer, wherein the fireproof layer adopts an intumescent fireproof coating, the transition layer adopts a primer, the first protection layer and the second protection layer adopt metal titanium foils, the first heat insulation layer adopts an aerogel felt, the second heat insulation layer adopts a phase change material, the phase change material is formed by compounding a phase change raw material and a base material, and the phase change raw material is microcapsules. A packaging material of the microcapsule is a mixture of melamine, formaldehyde and urea, and a phase change inner core of the microcapsule is paraffin; the base material is epoxy resin. The composite material not only has the characteristics of excellent fireproof and heat-insulating performance, thin thickness, light weight, good long-term stability and the like, but also has the advantages of simple structure, convenience in installation, wide application range and the like.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention is a divisional application of patent application number 202411150634.5, and its invention name is “A fireproof and heat-insulating integrated composite structure”. Technical Field

[0002] The invention relates to the technical field of fireproof and heat-insulating structures, and in particular to a composite material with excellent heat-insulating properties. Background Art

[0003] Fireproof and heat-insulating structures are key factors in protecting the safe operation of high-speed aircraft (such as missiles) and completing various tasks. Structures with excellent fireproof and heat-insulating effects can not only prevent the outer surface of the aircraft from being damaged by the aerodynamic thermal environment (the aerodynamic thermal environment will cause the surface temperature of the aircraft to rise, accompanied by thermal stress, strain, etc., thereby reducing the stiffness, strength and bearing capacity of the outer surface), but also avoid high temperatures in the aircraft cabin caused by heat transfer, thereby ensuring the stability of the internal performance of the aircraft. Traditionally, the heat insulation protection structure for the surface of aircraft mainly adopts the heat insulation layer method such as fiber felt coating and protective coating spraying. However, the coated fiber felt is in the aerodynamic thermal environment for a long time, which not only has the problems of heavy weight and high space occupancy rate, but also has the problems of large ablation retreat, poor long-term stability, and poor heat insulation performance, which cannot meet the needs of long-term flight operations of aircraft such as missiles in the aerodynamic thermal environment; although the spraying protective coating can reduce the weight and space occupancy rate to a certain extent, it is in the aerodynamic thermal environment for a long time, and it is easy to smoke, slag, crack, and fall off and peel off due to low bonding strength, causing the protective coating to lose its protective effect on the surface of the aircraft, and then causing the aircraft to be directly exposed to the aerodynamic thermal environment. It can be seen that the existing technology still lacks a heat insulation protection structure with both heat insulation and fire prevention functions, light weight, thin thickness, and good long-term stability for long-term aerodynamic thermal environment. Summary of the invention

[0004] In view of the problems existing in the above prior art, the object of the present invention is to provide a composite material with excellent thermal insulation performance, which has the advantages of good thermal insulation and fireproof performance, light weight, thin thickness, good long-term stability, and easy installation.

[0005] The purpose of the present invention is achieved through the following technical solutions: A composite material with excellent thermal insulation performance comprises a fireproof layer, a transition layer, a first protective layer, a first thermal insulation layer, a second thermal insulation layer and a second protective layer in sequence; wherein the fireproof layer adopts an intumescent fire retardant coating, the transition layer adopts a primer, the first protective layer and the second protective layer adopt metal titanium foil, the first thermal insulation layer adopts aerogel felt, and the second thermal insulation layer adopts a phase change material.

[0006] Based on the further optimization of the above scheme, the thickness of the fireproof layer is 0.6-1.0 mm; the intumescent fireproof coating includes a film former, a flame retardant and a functional filler, wherein the mass ratio of the film former, the flame retardant and the functional filler is 2-3:6-10:1-3. The film former is a high elastic polyurethane polymer (wherein the high elastic polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 5-8:4-7:2-4; the functional filler is composed of nano-aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres, and the mass ratio between them is 5-10:2-5:3-8. The particle size of the ultrafine ceramic hollow microspheres is 20-50 μm, and its melting point is not less than 1600°C.

[0007] The flame retardant composed of ammonium polyphosphate, pentaerythritol and melamine is combined with a film-forming material to expand and carbonize in a high-temperature environment to form a dense carbonized layer, thereby achieving the purpose of heat insulation and fire prevention; at the same time, functional fillers composed of nano-aluminum hydroxide, expanded graphite and ultra-fine ceramic hollow microspheres are used to, firstly, use nano-aluminum hydroxide to inhibit the amount of smoke and reduce material loss during the high-temperature carbonization process, secondly, enhance the strength of the carbonized layer through nano-aluminum hydroxide, and thirdly, fill the gaps in the expanded carbonized layer through expanded graphite and ultra-fine ceramic hollow microspheres, thereby enhancing the heat insulation performance of the carbonized layer.

[0008] Based on further optimization of the above solution, the transition layer uses epoxy primer, and the thickness of the transition layer is 40 to 60 μm; the bonding strength between the fireproof layer and the first protective layer is improved by the transition layer.

[0009] Based on the further optimization of the above scheme, the thickness of the first protective layer (when the first protective layer is flat) is 0.03-0.1mm; the first protective layer adopts a metal embossed titanium foil structure, that is, protrusions distributed in an array are arranged on the surface of the flat titanium foil structure. The shape of the protrusions is any one of rice grains, pearls, and water drops; the diameter of the protrusions is 1-2.5mm, and the height is 0.4-1.0mm; the distance between two adjacent protrusions is 4-8mm; the number of protrusions per unit area in the first protective layer is 1.5x10 4 ~6x10 4 indivual.

[0010] The protrusions of the first protective layer are arranged to improve the stiffness of the first protective layer through the strain hardening effect produced during the pressing process of the protrusions; the roughness of the transition layer corresponding to the first protective layer is increased through the distribution of the protrusions, and the interface bonding force between the first protective layer and the fireproof layer is increased by using the transition layer; the wrinkles formed during the molding process of the protective layer are reduced through the preparation of the protrusions, thereby reducing the weak points of failure, avoiding damage to the protective layer, and improving the overall liquid penetration resistance of the composite material; the protrusions provide a buffer gap for the fireproof layer to ensure that the fireproof layer completes expansion and carbonization while avoiding the expansion of the fireproof layer. The first is to prevent cracking, falling off and other problems caused by impact force; the second is to convert the reflective surface from mirror reflection to dot matrix diffuse reflection through uneven protrusions, thereby expanding the heat reflection area and improving the reflection efficiency; the third is to utilize the continuous uneven protrusions to cooperate with the first thermal insulation layer to form a plurality of cavity matrices, thereby changing the interlayer flow field and forming micro air gaps, effectively blocking heat conduction, inhibiting heat convection, and improving the thermal insulation effect; the fourth is to achieve point contact between the first protective layer and the first thermal insulation layer, thereby reducing heat conduction between the first protective layer and the first thermal insulation layer, so that the heat is effectively dissipated in the cavity matrix, further improving the thermal insulation effect.

[0011] Based on further optimization of the above scheme, the first thermal insulation layer adopts basalt fiber reinforced silica aerogel felt, and the thickness of the first thermal insulation layer is 2 to 5 mm; wherein, the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.78 to 1, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.017 to 0.020 W / (m•K). Using small diameter basalt fibers as reinforcing fibers for nanoporous silica aerogel can effectively limit the solid heat conduction of the fibers themselves, making the basalt fiber felt itself have a lower thermal conductivity. At the same time, using short diameter basalt fibers to form a low volume density preform can further reduce its volume density while ensuring the mechanical properties of the fiber-reinforced aerogel composite material. The diameter of the fiber preform is close to the wavelength of near-infrared radiation, which can produce a strong diffraction and scattering effect on the near-infrared radiation, thereby further enhancing the high-temperature infrared radiation heat conduction barrier effect. In addition, the addition of basalt fibers can effectively solve the problems of pure aerogel being brittle and easy to break. The volume density of the basalt fiber reinforced silica aerogel felt is 150-170 kg / m 3 The bulk density of the preform formed by basalt fiber is 80~90kg / m 3 The density of silica aerogel is 70~80kg / m 3 .

[0012] Based on the further optimization of the above scheme, the thickness of the second thermal insulation layer is 2-5 mm; the phase change material is composited by a phase change raw material and a matrix material, the phase change raw material is a microcapsule, the particle size of the microcapsule is 10-100 μm, wherein the encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea (through the combination of urea and a specific formula, the formaldehyde residue is effectively reduced to avoid affecting the coating performance of the encapsulation material), the phase change core of the microcapsule is paraffin; the matrix material is epoxy resin; the phase change temperature of the phase change material is 95-120 ° C, and the density is 1.0-1.3 g / cm 3 , the phase change enthalpy value is 220-260 J / g. The mass ratio between the epoxy resin (matrix material) and the microcapsule (phase change raw material) is 1:1-15; the mass ratio between the microcapsule encapsulation material (i.e. melamine formaldehyde resin) and paraffin is 6:1; the mass ratio of melamine and formaldehyde urea in the encapsulation material is 10:20-30:1-5.

[0013] Based on further optimization of the above solution, the thickness of the second protective layer is 0.03-0.1 mm, and the second protective layer is a flat and smooth metal titanium foil, which facilitates the installation of the second protective layer.

[0014] The following are the effects of the technical solution of the present invention: The composite material of the present invention utilizes the dense heat-insulating layer formed by the expansion and carbonization of the fire-proof layer of the intumescent fire-retardant coating to block flames and isolate heat, and through the close and stable combination between the fire-proof layer, the transition layer, and the first protective layer, not only the heat reflection and blocking effect are improved, but also effective buffering is provided for the fire-proof layer that expands when heated, and problems such as peeling and cracking due to space limitations during the expansion process are avoided, and the integrity between the fire-proof layer, the transition layer, the first protective layer, and the first heat-insulating layer is improved, and the heat-insulating effect of the composite material is further improved. Afterwards, the cooperation between the first protective layer, the second protective layer and the first heat-insulating layer and the second heat-insulating layer is utilized to not only protect the first heat-insulating layer and the second heat-insulating layer, and to avoid problems such as damage and separation of the first heat-insulating layer and the second heat-insulating layer during the heat-protection process, but also effective heat protection is achieved through the coordinated cooperation between the first heat-insulating layer and the second heat-insulating layer, while ensuring that the overall weight of the composite material is light and the thickness is thin, and the effect of heat-insulating protection is further improved. In addition, the composite material provided by the present invention not only has the characteristics of excellent fireproofing and heat insulation performance, thin thickness, light weight, etc., but also has the advantages of simple structure, easy installation, and wide application range. It can be used for fireproofing and heat insulation of hot end components of various equipment in high temperature environments of 800°C to 1200°C. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Schematic diagram of the composite material in the embodiment of the present invention.

[0016] Figure 2 Schematic diagram of the structure of the first protective layer of the composite material in an embodiment of the present invention.

[0017] Among them, 10, fireproof layer; 20, transition layer; 30, first protective layer; 40, first thermal insulation layer; 50, second thermal insulation layer; 60, second protective layer. DETAILED DESCRIPTION

[0018] The present invention is further described in detail in conjunction with the following specific embodiments and drawings. The process, conditions, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention has no special restrictions; in addition, the described embodiments are not intended to further limit the present invention.

[0019] Embodiment 1: A composite material with excellent thermal insulation properties, such as Figure 1 As shown: it includes a fireproof layer 10, a transition layer 20, a first protective layer 30, a first heat-insulating layer 40, a second heat-insulating layer 50 and a second protective layer 60 in sequence; wherein the thickness of the fireproof layer 10 is 0.6 mm, and the fireproof layer 10 adopts an intumescent fire-retardant coating, and the intumescent fire-retardant coating includes a film-forming material, a flame retardant and a functional filler, wherein the mass ratio of the film-forming material, the flame retardant and the functional filler is 2:6:1; the film-forming material is a high-elasticity polyurethane polymer (wherein the high-elasticity polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 5:4:2; the functional filler is composed of nano-aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres (the average particle size of the ultrafine ceramic hollow microspheres is 20μm, and the melting point is not less than 1600℃), and the mass ratio between them is 5:2:3.

[0020] The transition layer 20 is made of epoxy primer, and the thickness of the transition layer 20 is 40 μm. The transition layer 20 is used to enhance the bonding strength between the fireproof layer 10 and the first protective layer 30. The thickness of the first protective layer 30 (when the first protective layer 30 is flat) is 0.03 mm. The first protective layer 30 is made of a metal embossed titanium foil structure, that is, protrusions (such as Figure 2 As shown, to ensure the multiple effects of the first protective layer 30, the protrusions are oriented toward the transition layer 20). The shape of the protrusions is rice grain-like; the diameter of the protrusions is 1 mm and the height is 0.4 mm; the distance between two adjacent protrusions is 4 mm; the number of protrusions per unit area in the first protective layer 30 is 6x10 4 indivual.

[0021] The first thermal insulation layer 40 is made of basalt fiber reinforced silica aerogel felt, and the thickness of the first thermal insulation layer 40 is 2 mm; wherein the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.78, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.020 W / (m•K); the volume density of the basalt fiber reinforced silica aerogel felt is 159.74 kg / m 3 The bulk density of the preform formed by basalt fiber is 89.74kg / m 3 The density of silica aerogel is 70kg / m 3 The thickness of the second thermal insulation layer 50 is 2 mm. The second thermal insulation layer 50 adopts phase change material, which is composed of a phase change raw material and a matrix material. The phase change raw material is a microcapsule, and the average particle size of the microcapsule is 30 μm. The encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the mass ratio of melamine, formaldehyde and urea in the encapsulation material is 10:20:1. The phase change core of the microcapsule is paraffin, and the mass ratio between the encapsulation material (i.e., melamine formaldehyde resin) and the paraffin is 6:1. The matrix material is epoxy resin, and the mass ratio between epoxy resin (matrix material) and microcapsule (phase change raw material) is 1:2. The phase change temperature of the phase change material is 95°C, and the density is 1.0 g / cm 3 , phase change enthalpy is 220J / g.

[0022] The thickness of the second protective layer 60 is 0.03 mm. The second protective layer 60 is a flat and smooth metal titanium foil, which facilitates the installation of the second protective layer 60 .

[0023] Embodiment 2: A composite material with excellent thermal insulation properties, such as Figure 1 As shown: it includes a fireproof layer 10, a transition layer 20, a first protective layer 30, a first heat-insulating layer 40, a second heat-insulating layer 50 and a second protective layer 60 in sequence; wherein the thickness of the fireproof layer 10 is 0.8 mm, and the fireproof layer 10 adopts an intumescent fire-retardant coating, and the intumescent fire-retardant coating includes a film-forming material, a flame retardant and a functional filler, wherein the mass ratio of the film-forming material, the flame retardant and the functional filler is 2.5:8:2; the film-forming material is a high-elasticity polyurethane polymer (wherein the high-elasticity polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 6:5:3; the functional filler is composed of nano-aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres (the average particle size of the ultrafine ceramic hollow microspheres is 35μm, and the melting point is not less than 1600℃), and the mass ratio between them is 8:3:5.

[0024] The transition layer 20 is made of epoxy primer, and the thickness of the transition layer 20 is 50 μm. The transition layer 20 is used to enhance the bonding strength between the fireproof layer 10 and the first protective layer 30. The thickness of the first protective layer 30 (when the first protective layer 30 is flat) is 0.06 mm. The first protective layer 30 is made of a metal embossed titanium foil structure, that is, protrusions (such as Figure 2 As shown, to ensure the multiple effects of the first protective layer 30, the protrusions are oriented toward the transition layer 20). The protrusions are pearl-shaped; the diameter of the protrusions is 1.5 mm and the height is 0.7 mm; the distance between two adjacent protrusions is 6 mm; the number of protrusions per unit area in the first protective layer 30 is 3.5x10 4 indivual.

[0025] The first thermal insulation layer 40 is made of basalt fiber reinforced silica aerogel felt, and the thickness of the first thermal insulation layer 40 is 3 mm; wherein, the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.85, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.018 W / (m•K); the volume density of the basalt fiber reinforced silica aerogel felt is 163.24 kg / m 3 The bulk density of the preform formed by basalt fiber is 88.24kg / m 3 The density of silica aerogel is 75kg / m 3 The thickness of the second thermal insulation layer 50 is 3 mm. The second thermal insulation layer 50 adopts phase change material, which is composed of a phase change raw material and a matrix material. The phase change raw material is a microcapsule, and the average particle size of the microcapsule is 60 μm. The encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the mass ratio of melamine, formaldehyde and urea in the encapsulation material is 10:25:3. The phase change core of the microcapsule is paraffin, and the mass ratio between the encapsulation material (i.e., melamine formaldehyde resin) and the paraffin is 6:1. The matrix material is epoxy resin, and the mass ratio between epoxy resin (matrix material) and microcapsule (phase change raw material) is 1:6. The phase change temperature of the phase change material is 110°C, and the density is 1.2 g / cm 3 , phase change enthalpy is 240J / g.

[0026] The thickness of the second protective layer 60 is 0.06 mm. The second protective layer 60 is a flat and smooth metal titanium foil, which facilitates the installation of the second protective layer 60 .

[0027] Embodiment 3: A composite material with excellent thermal insulation properties, such as Figure 1As shown: it includes a fireproof layer 10, a transition layer 20, a first protective layer 30, a first heat-insulating layer 40, a second heat-insulating layer 50 and a second protective layer 60 in sequence; wherein the thickness of the fireproof layer 10 is 1.0 mm, and the fireproof layer 10 adopts an intumescent fire-retardant coating, and the intumescent fire-retardant coating includes a film-forming material, a flame retardant and a functional filler, wherein the mass ratio of the film-forming material, the flame retardant and the functional filler is 3:10:3; the film-forming material is a high-elasticity polyurethane polymer (wherein the high-elasticity polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 8:7:4; the functional filler is composed of nano-aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres (the average particle size of the ultrafine ceramic hollow microspheres is 50 μm, and the melting point is not less than 1600°C), and the mass ratio between them is 10:5:8.

[0028] The transition layer 20 is made of epoxy primer, and the thickness of the transition layer 20 is 60 μm. The transition layer 20 is used to enhance the bonding strength between the fireproof layer 10 and the first protective layer 30. The thickness of the first protective layer 30 (when the first protective layer 30 is flat) is 0.1 mm. The first protective layer 30 is made of a metal embossed titanium foil structure, that is, protrusions (such as Figure 2 As shown, to ensure the multiple effects of the first protective layer 30, the protrusions are oriented toward the transition layer 20). The protrusions are in the shape of a water drop; the diameter of the protrusions is 2.5 mm and the height is 1.0 mm; the distance between two adjacent protrusions is 8 mm; the number of protrusions per unit area in the first protective layer 30 is 1.5x10 4 indivual.

[0029] The first thermal insulation layer 40 is made of basalt fiber reinforced silica aerogel felt, and the thickness of the first thermal insulation layer 40 is 5 mm; wherein the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:1, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.017 W / (m•K); the volume density of the basalt fiber reinforced silica aerogel felt is 160 kg / m 3 The bulk density of the preform formed by basalt fiber is 80kg / m 3 , the density of silica aerogel is 80kg / m 3The thickness of the second thermal insulation layer 50 is 5 mm. The second thermal insulation layer 50 adopts phase change material, which is composed of a phase change raw material and a matrix material. The phase change raw material is a microcapsule, and the average particle size of the microcapsule is 80 μm. The encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the mass ratio of melamine, formaldehyde and urea in the encapsulation material is 10:30:5. The phase change core of the microcapsule is paraffin, and the mass ratio between the encapsulation material (i.e., melamine formaldehyde resin) and the paraffin is 6:1. The matrix material is epoxy resin, and the mass ratio between epoxy resin (matrix material) and microcapsule (phase change raw material) is 1:8. The phase change temperature of the phase change material is 120°C, and the density is 1.3 g / cm 3 , phase change enthalpy is 260J / g.

[0030] The thickness of the second protective layer 60 is 0.1 mm. The second protective layer 60 is a flat and smooth metal titanium foil, which facilitates the installation of the second protective layer 60 .

[0031] Comparative Example 1: A composite material comprises a fireproof layer, a transition layer, a first protective layer, a first thermal insulation layer, a second thermal insulation layer and a second protective layer in sequence, wherein the thickness and material of the fireproof layer, the transition layer, the first thermal insulation layer, the second thermal insulation layer and the second protective layer are consistent with those in Example 2; the thickness of the first protective layer is 0.06 mm and the first protective layer is a flat and smooth metal titanium foil.

[0032] Comparative Example 2: A composite material comprises a fireproof layer, a transition layer, a first protective layer, a heat-insulating layer A and a second protective layer in sequence, wherein the thickness and material of the fireproof layer, the transition layer, the first protective layer and the second protective layer are consistent with those in Example 2; the heat-insulating layer A adopts basalt fiber reinforced silica aerogel felt, and the thickness of the heat-insulating layer A is 6 mm; wherein the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of the basalt fiber to the silica aerogel is 1:0.85, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.018 W / (m•K); the volume density of the basalt fiber reinforced silica aerogel felt is 163.24 kg / m 3 The bulk density of the preform formed by basalt fiber is 88.24kg / m 3 The density of silica aerogel is 75kg / m 3 .

[0033] Comparative Example 3: A composite material comprises a fireproof layer, a transition layer, a first protective layer, a heat-insulating layer B and a second protective layer in sequence, wherein the thickness and materials of the fireproof layer, the transition layer, the first protective layer and the second protective layer are consistent with those in Example 2; the thickness of the heat-insulating layer B is 6 mm; the heat-insulating layer B adopts a phase change material, the phase change material is composited by a phase change raw material and a matrix material, the phase change raw material is a microcapsule, the average particle size of the microcapsule is 60 μm, wherein the encapsulating material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the mass ratio of melamine, formaldehyde and urea in the encapsulating material is 10:25:3; the phase change core of the microcapsule is paraffin, and the mass ratio of the encapsulating material (i.e., melamine formaldehyde resin) to the paraffin is 6:1; the matrix material is epoxy resin, and the mass ratio of the epoxy resin (matrix material) to the microcapsule (phase change raw material) is 1:6; the phase change temperature of the phase change material is 110°C, and the density is 1.2 g / cm 3 , phase change enthalpy is 240J / g.

[0034] Comparative Example 4: A composite material comprises a fireproof layer, a transition layer, a first protective layer, a first heat-insulating layer, a second heat-insulating layer and a second protective layer in sequence, wherein the thickness and material of the transition layer, the first protective layer, the first heat-insulating layer, the second heat-insulating layer and the second protective layer are consistent with those in Example 2; the thickness of the fireproof layer 10 is 0.8 mm, and the fireproof layer 10 adopts an intumescent fire-retardant coating, and the intumescent fire-retardant coating comprises a film-forming material, a flame retardant and a functional filler, wherein the mass ratio between the film-forming material, the flame retardant and the functional filler is 2.5: 8:2; the film-forming material is a high-elastic polyurethane polymer (wherein the high-elastic polyurethane polymer is polymerized by one or two of polycaprolactone diol and polyether diol and aliphatic polyisocyanate HDI); the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 6:5:3; the functional filler is composed of expanded graphite and ultrafine ceramic hollow microspheres (the average particle size of the ultrafine ceramic hollow microspheres is 35μm, and the melting point is not less than 1600℃), and the mass ratio between them is 3:5.

[0035] The composite material samples prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were respectively fixed on the tooling of the inner cavity of the heating device, and three temperature sensors were arranged on the cold surface of the sample and evenly distributed on the cold surface of the sample. When the ambient temperature was 23°C (the other test conditions were also the same) and the hot surface temperature was 800°C, the cold surface temperatures of the corresponding samples were obtained, and the test time was 300s. The test results are as follows:

[0036] As shown in the table above: the use of the structural combination of the specific fireproof layer, transition layer, first protective layer, first thermal insulation layer, second thermal insulation layer, and second protective layer of the present application in combination with the specific material combination of the corresponding structural layer can effectively improve the fireproof and thermal insulation properties of the composite material. Under the action of a long period of time (i.e., 300s) at a hot surface temperature of 800°C, the average cold surface temperature of the composite material prepared by the present application is not greater than 60°C, which is significantly lower than that of the composite materials prepared in Comparative Examples 1 to 4; at the same time, the temperature difference of each temperature measuring point of the composite material prepared by the present application is small, proving that the structure of the present application can dissipate heat evenly without temperature concentration points, while the temperature deviation of the temperature measuring points of the composite materials in Comparative Examples 1 to 4 is large, which also indirectly proves that the interlayer thermal insulation effect of the present application is good.

Claims

1. A composite material with excellent thermal insulation performance, characterized in that: It includes a fireproof layer, a transition layer, a first protective layer, a first heat-insulating layer, a second heat-insulating layer and a second protective layer in sequence; wherein the fireproof layer adopts an intumescent fire-retardant coating, the transition layer adopts a primer, the first protective layer and the second protective layer adopt metal titanium foil, the first heat-insulating layer adopts aerogel felt, and the second heat-insulating layer adopts a phase change material; The thickness of the second thermal insulation layer is 2 to 5 mm; the phase change material is composed of a phase change raw material and a matrix material, the phase change raw material is a microcapsule, the particle size of the microcapsule is 10 to 100 μm, wherein the encapsulation material of the microcapsule is a mixture of melamine, formaldehyde and urea, and the phase change core of the microcapsule is paraffin; the matrix material is epoxy resin; the phase change temperature of the phase change material is 95 to 120 ° C, and the density is 1.0 to 1.3 g / cm 3 , phase change enthalpy value is 220~260J / g; the mass ratio between epoxy resin and microcapsule is 1:1~15; the mass ratio between microcapsule packaging material and paraffin is 6:1; the mass ratio of melamine and formaldehyde urea in the packaging material is 10:20~30:1~5.

2. A composite material with excellent thermal insulation performance according to claim 1, characterized in that: The thickness of the fireproof layer is 0.6-1.0 mm; the intumescent fireproof coating comprises a film-forming material, a flame retardant and a functional filler, wherein the mass ratio of the film-forming material, the flame retardant and the functional filler is 2-3:6-10:1-3.

3. A composite material with excellent thermal insulation performance according to claim 1 or 2, characterized in that: The film-forming material is a high-elastic polyurethane polymer; the flame retardant is composed of ammonium polyphosphate, pentaerythritol and melamine, and the mass ratio between them is 5-8:4-7:2-4; the functional filler is composed of nano-grade aluminum hydroxide, expanded graphite and ultrafine ceramic hollow microspheres, and the mass ratio between them is 5-10:2-5:3-8.

4. A composite material with excellent thermal insulation performance according to claim 1 or 3, characterized in that: The transition layer adopts epoxy primer, and the thickness of the transition layer is 40-60 μm.

5. The composite material with excellent thermal insulation performance according to claim 4, characterized in that: The thickness of the first protective layer is 0.03-0.1 mm; the first protective layer adopts a metal embossed titanium foil structure, that is, protrusions distributed in an array are arranged on the surface of the flat titanium foil structure.

6. A composite material with excellent thermal insulation performance according to claim 5, characterized in that: The shape of the protrusion is any one of rice grain shape, pearl shape and water drop shape.

7. The composite material with excellent thermal insulation performance according to claim 4, characterized in that: The first thermal insulation layer uses basalt fiber reinforced silica aerogel felt, and the thickness of the first thermal insulation layer is 2 to 5 mm; wherein the diameter of the basalt fiber is not greater than 6 μm, the mass ratio of basalt fiber to silica aerogel is 1:0.78 to 1, and the thermal conductivity of the basalt fiber reinforced silica aerogel felt at room temperature is 0.017 to 0.020 W / (m•K).

8. The composite material with excellent thermal insulation performance according to claim 7, characterized in that: The volume density of the basalt fiber reinforced silica aerogel felt is 150-170 kg / m 3 The bulk density of the preform formed by basalt fiber is 80~90kg / m 3 The density of silica aerogel is 70~80kg / m 3 .

9. The composite material with excellent thermal insulation performance according to claim 1, characterized in that: The thickness of the second protective layer is 0.03-0.1 mm, and the second protective layer is a flat and smooth metal titanium foil.

Citation Information

Patent Citations

  • Integrally-arranged capacitor and manufacturing method thereof

    CN103578747A

  • Double-component expansion type fireproof coating and preparation method thereof

    CN110591502A

  • Water-based fireproof coating suitable for railway vehicle chassis and preparation method thereof

    CN110591509A

  • Fire-proof and heat-insulating metal plate and preparation method thereof

    CN110667203A

  • Variable phase-change temperature coating as well as preparation method and application thereof

    CN117186715A

Cited By

  • Fireproof heat-insulation water-based decorative plate and preparation method thereof

    CN120921762A

  • Phase-change temperature-control photovoltaic support mechanism, preparation method thereof and BIPV (building integrated photovoltaics) system

    CN120956171A

  • Phase change temperature control photovoltaic support mechanism, preparation method thereof and BIPV system

    CN120956171B

  • Thermal insulation travertine ceramic tile and preparation method thereof

    CN121135397A